Analysis of Parenting Styles and The Role of Teachers in Social Character Value Socialization During The Covid ’19 Pandemic - Dwijayanti, Yeni Rahma; Khoiriyyah, Amilatul; Lailiyah, Faridatul (Psikoscientia, 2024)
Schools, as formal institutions, are required to be able to involve the school community throughout the learning process. Teachers and parents have an important role, considering that both are directly involved in the learning process. Moreover, changes in the learning system during the COVID-19 pandemic in 2020–2022 are a challenge in implementing changes in social character values. The network of teachers and parents must work together to minimize the impact of changes in social character values for the younger generation that can lead to friction or conflict. Facts show that it is not uncommon for sudden social changes to affect social character values in the younger generation, both in the academic environment and in their social environment. Therefore, education has a strategic role in socializing social character values for the younger generation during the 2020–2022 pandemic. The method used is qualitative from the perspective of Peter L. Berger and Thomas Luckman's socialization theory. The results show that the socialization of social character values carried out by teachers and parents is strongly influenced by the construction of society. Parents as primary socialization agents have an important role in internalizing the young generation when they are in the home environment, while teachers as secondary socialization agents play an important role in internalizing the school environment. Internalization carried out by teachers and parents determines the younger generation to objectify and externalize in their social life during the 2020–2022 pandemic. This is done to form young people who are characterized as smart and become good citizens in various social situations